Creativity and Personhood in the theology of prot. Georges Florovsky - Totorysan, Roussina (Forum Theologicum Sardicense, 2025)
The author endeavors to create a synthesis within the broader theological system of prot. Georges Florovsky of his understanding of personhood and creativity as task and duty of the human being. After considering the larger theological setting of the question another approach is then suggested, outlining a contextualization of the theology of personhood within the ecclesiological understanding of Florovsky, but without stepping into the latter debates and developments of his students.